Robin Law (ed.): From Slave Trade to ‘Legitimate ’ Commerce. The Commercial Transition in Nineteenth-century West Africa - Gausset, Quentin (Tidsskriftet Antropologi, 1999)
The Commercial Transition in Nineteenth-century West Africa Anmeldes af Quentin Gausset